New oral anticoagulants in thromboembolism prevention in nonvalvular atrial fibrillation - Sosa Rosado, José Manuel (2013)
Atrial fibrillation is the most frequent cardiac arrhythmia in clinical practice. The value of anticoagulation with vitamin K antagonists like warfarin in the prevention of embolic phenomena is widely demonstrated but managing is difficult because of its known interactions with other drugs and even food. Looking for the ideal anticoagulant in the last years new antithrombotic agents have appeared and others are in advanced phases of investigation. In the current review results of new anticoagulant agents development and expectations, opportunities and challenges are described in regards to direct thrombin and Xa factor inhibitors.